KONSUMSI DAN PRAKTIK MODERNITAS DALAM IKLAN ENAMEL ZAMAN KOLONIAL DI HINDIA - Karina Rima Melati (Ars: Jurnal Seni Rupa dan Desain, 2008)
indonesia in netherlands colonization era experienced a western modern industrialization which was signified by liberal economic system application. This economic system led to the production of new regulation and mass communication media, including commercial advertisements. Advertisements which were actually persuasive messages of the offered product and service conveyed to the target audiences played a role in constructing a dynamic consumption culture and supporting the existing modern industries. One type of it was the enamel advertisement. It was made of a 2-3 millimeterthick iron plaque with an eye- catching visualization so that it attracted a lot of attention from the people.This kind of advertisement became a crucial part to translate the consumers’ taste which was built in the consumptive culture dynamics. Its verbal and visual signs revealed the employed social- economic system of the target audiences.            Keywords: artefact of modern industry